2022
DOI: 10.1039/d2cp00678b
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of Ru clusters during nitrogen dissociation in ammonia synthesis

Abstract: The dynamic evolution of catalyst structures greatly influences the reactivity, especially sub-nanometer clusters, exhibiting complex configurational fluctuation. In the present work, we study the structural dynamics of a Ru19 cluster...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…5a and b). Furthermore, Cheng used Ru 19 clusters as an example to calculate the free energy distribution of a typical catalytic reaction 84 based on ab initio molecular 85 Under 400 °C and 3 MPa conditions, the TOF Ru of 0.5Ru-SNC (0.067 s −1 ) was 3.5 times higher than that of the 1.2Ru-NPs catalyst (0.019 s −1 ). The UV-vis and in situ infrared experiments showed that the N 2 H 4 species was the main intermediate for NH 3 synthesis on the Ru-SNCs catalyst.…”
Section: Noble Metal Sccsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a and b). Furthermore, Cheng used Ru 19 clusters as an example to calculate the free energy distribution of a typical catalytic reaction 84 based on ab initio molecular 85 Under 400 °C and 3 MPa conditions, the TOF Ru of 0.5Ru-SNC (0.067 s −1 ) was 3.5 times higher than that of the 1.2Ru-NPs catalyst (0.019 s −1 ). The UV-vis and in situ infrared experiments showed that the N 2 H 4 species was the main intermediate for NH 3 synthesis on the Ru-SNCs catalyst.…”
Section: Noble Metal Sccsmentioning
confidence: 99%
“…5a and b ). Furthermore, Cheng used Ru 19 clusters as an example to calculate the free energy distribution of a typical catalytic reaction 84 based on ab initio molecular dynamics (AIMD) and free energy methods. It was found that the reaction free energies (DrG) and barrier (DGa) of the Ru 19 clusters were quite different from those obtained from static geometric optimization methods, indicating that the dynamic fluctuations of clusters configurations significantly affected the reaction free energy and potential barrier.…”
Section: Sccs For Nh 3 Synthesismentioning
confidence: 99%
“…20 Very recently, the role of small Ru clusters for achieving ammonia synthesis under mild conditions has been evoked though their structural dynamics. 29 For ammonia dissociation on Ru(0001), the rate-determining step is the recombination of adsorbed atomic nitrogen into the N 2 product, of which the activation barrier is sensitive to atomic nitrogen surface coverage (E act = 51.0 − 43.8 × θ N kcal mol −1 ). 24 This is supported by a more recent theoretical investigation of Ru(0001), Ru(111), and Ir(111) surfaces, which involves DFT-based temperature-programmed desorption spectra simulations compared to measurements.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Concerning ammonia synthesis ,,, and decomposition ,, on ruthenium extended surfaces and clusters modeled in idealistic condition (vacuum), DFT calculations of NH 3 synthesis on Ru(0001) demonstrate that N 2 dissociation is the rate-determining step of the reaction mechanism . Very recently, the role of small Ru clusters for achieving ammonia synthesis under mild conditions has been evoked though their structural dynamics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation